The political relevance of a love story: Thomas Otway’s interpretation of Shakespeare’s Romeo and Juliet - E. M. Lutsenko (Шаги, 2024)
The article is devoted to the reception of Shakespeare’s works in England in the last third of the 17th century, when Shakespeare’s plays were rewritten for the stage and adapted to the contemporary conditions and rules of English drama. Thomas Otway is considered one of the major translator-interpreters of Shakespeare plays into the language of his own modernity. The article examines how Otway treats the love story of Romeo and Juliet, namely, which elements he rewrites, which are left exactly as in Shakespeare’s Romeo and Juliet, and which are completely removed from the text of Otway’s play. Thus, the adaptation is regarded as a kind of translation within the framework of a single national tradition — from the language of the Elizabethan era to the language of the Restoration. Of particular importance are the changes made by Otway to the final episode of the play (the lovers get a chance to say goodbye to each other before their death, which does not exist in Shakespeare’s play). It is also important to mention that Otway’s play reflects the political situation of his epoch. Otway’s interpretation influenced all subsequent adaptations and European (German and French) translations of the 18th century.